A paradigmatic autistic phenotype associated with loss of PCDH11Y and NLGN4Y genes - Rosaria Nardello; Vincenzo Antona; Giuseppe Donato Mangano; Vincenzo Salpietro; Salvatore Mangano; Antonina Fontana (BMC, 2021)
Abstract Background Most studies relative to Y chromosome abnormalities are focused on the sexual developmental disorders. Recently, a few studies suggest that some genes located on Y chromosome may be related to different neurodevelopment disorders. Case presentation We report a child with sexual developmental disorder associated with a peculiar phenotype characterized by severe language impairment and autistic behaviour associated with a mosaicism [45,X(11)/46,XY(89)] and a partial deletion of the short and long arm of Y chromosome (del Yp11.31q11.23) that also involves the loss of both PCDH11Y and NLGN4Y genes. To our knowledge no study has ever reported the occurrence of the lack of both PCDH11Y and NLGN4Y located in the Y chromosome in the same patient. Conclusions We hypothesized a functional complementary role of PCDH11Y and NLGN4Y within formation/maturation of the cerebral cortex. The impairment of early language development may be mainly related to the lack of PCDH11Y that underlies the early language network development and the later appearance of the autistic behaviour may be mainly related to deficit of inhibitory glicinergic neurotransmission NLGN4Y-linked.